2020
DOI: 10.1152/ajplung.00408.2019
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposures to electronic-cigarette aerosols impair the Wnt signaling during mouse lung development

Abstract: Currently, more than 9 million American adults, including women of childbearing age, use electronic-cigarettes (e-cigs). Further, the prevalence of maternal vaping now approaching 10% is similar to that of maternal smoking. Little, however, is known about the effects of fetal exposures to nicotine-rich e-cig aerosols on lung development. In this study, we assessed whether in utero exposures to e-cig aerosols compromised lung development in mice. A third-generation e-cig device was used to expose pregnant BALB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 114 publications
(222 reference statements)
4
59
0
7
Order By: Relevance
“…1) may not be solely responsible for the cellular toxicity (Figs. 4, 5, 6, 7, 8), but that the intrinsic toxicity of the flavoring chemical, such as the well-known deleterious effects of cinnamaldehyde [36,[46][47][48][49][50], may also play a significant role. Overall, we showed (1) that sub-ohm (0.15 Ω) vaping produces more toxic chemicals than regular (1.5 Ω) vaping, and that this can be flavor specific; and (2) that sub-ohm vaping induces detrimental effects to human lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1) may not be solely responsible for the cellular toxicity (Figs. 4, 5, 6, 7, 8), but that the intrinsic toxicity of the flavoring chemical, such as the well-known deleterious effects of cinnamaldehyde [36,[46][47][48][49][50], may also play a significant role. Overall, we showed (1) that sub-ohm (0.15 Ω) vaping produces more toxic chemicals than regular (1.5 Ω) vaping, and that this can be flavor specific; and (2) that sub-ohm vaping induces detrimental effects to human lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…1), the enhanced toxicity of the cinnamon-flavored e-cig aerosol (Figs. 4, 7, 8) may be due to cinnamaldehyde, the primary flavoring chemical of cinnamon-based e-liquids, which was shown to be highly toxic in both in vitro and in vivo models [36,[46][47][48][49][50]64]. For instance, using a zebrafish model it was shown that the presence of cinnamaldehyde in various e-liquids, including in bubble gum flavored-e-liquids, was mainly responsible for the harmful developmental effects observed [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that maternal exposure to systemic nicotine interferes with airway and airspace development in animal models [1,2]. Recent efforts have further characterized transplacental effects of maternal nicotine and e-cigarette vapor on fetal lung development and introduced the concept of susceptibilities to injury in various compartments that may persist into adulthood [3][4][5].…”
mentioning
confidence: 99%